2017
DOI: 10.1097/ccm.0000000000002485
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation for Acute Decompensated Heart Failure

Abstract: Among this selected cohort of 105 patients implanted with venoarterial-extracorporeal membrane oxygenation for acute decompensated heart failure, 1-year survival was 42%, but better for patients with pre-extracorporeal membrane oxygenation Sequential Organ Failure Assessment scores of less than 11. Venoarterial-extracorporeal membrane oxygenation should be considered for patients with acute decompensated heart failure, but timing of implantation is crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 21 publications
2
48
1
Order By: Relevance
“…Equally, arterial lactate will not be in influenced by arterial carbon dioxide pressure levels, whereas arterial pH will. Arterial lactate has in agreement with our study also been found to be an independent pre‐VA‐ECMO predictor of short and midterm survival in several other studies with selected or unselected patients’ populations . Our finding of an odds ratio of 1.15 per mmol/L implies that the mortality risk increases 10‐fold at a lactate level of 10 mmol/L.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Equally, arterial lactate will not be in influenced by arterial carbon dioxide pressure levels, whereas arterial pH will. Arterial lactate has in agreement with our study also been found to be an independent pre‐VA‐ECMO predictor of short and midterm survival in several other studies with selected or unselected patients’ populations . Our finding of an odds ratio of 1.15 per mmol/L implies that the mortality risk increases 10‐fold at a lactate level of 10 mmol/L.…”
Section: Discussionsupporting
confidence: 92%
“…Previous larger studies have presented a combination of nonsurgical and surgical patients including both predictors before and during VA‐ECMO , or have not reported rate of missing data or having substantially incomplete data . The largest and only single center study strictly addressing the impact of pre‐ECMO variables on outcome by Waha et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Extracorporeal Life Support Organization states that contraindications to V‐A ECMO include chronic organ dysfunction . Veno‐arterial ECMO is indicated for decompensated chronic heart failure patients, but their mortality is high . Few reports of V‐A ECMO for septic shock patients with chronic heart failure exist.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pre‐existing chronic heart failure is not a contraindication for VA‐ECMO in septic cardiomyopathy patients. A pre‐ECMO SOFA score >11, idiopathic cardiomyopathy as the cause of pre‐existing chronic heart failure, cardiac disease duration >2 years pre‐ECMO, and pre‐ECMO blood lactate >4 mmol/L are independent predictors of 1‐year mortality in patients receiving V‐A ECMO for acute decompensated heart failure . Regarding septic cardiomyopathy in chronic heart failure, the SOFA score and blood lactate level might not be mortality predictors because both are affected by sepsis itself, in addition to cardiogenic shock.…”
Section: Discussionmentioning
confidence: 99%